A dual porosity poroelastic model for simulation of gas flow in saturated claystone as a potential host rock for deep geological repositories. (September 2021) - Yang, Jianxiong; Fall, Mamadou
Highlights: Claystone is a potential host rock for radioactive waste disposal. Gas migration in host rocks can jeopardize the safety of a repository. A fully coupled HM model is developed to simulate the gas transport in claystone. Main experimental behaviors are well captured by the HM model. Dilation/compression of the matrix contribute to the closure/opening of fractures. Abstract: Claystone is considered as a potential host rock for radioactive waste disposal at great depth in many countries. Considerable quantity of gas can be generated in a deep geological repository (DGR) due to several processes, which may affect the integrity of the host rock and the safety of the DGR. Thus, understanding the migration of gas through the host rock is an essential requirement in developing a safety case for a deep geological disposal of radioactive waste. In this paper, a fully coupled dual porosity poroelastic model is developed to simulate the gas transport process in initially saturated claystone. The model considers the hydro-mechanical behavior for the fractured porous medium consisting of both the porous matrix (represented by the porous continuum) and fractures (represented by the fractured continuum), which are two separate and overlapping porous media. Each continuum has its own constitutive law that imposes a superimposed effect on the behavior of the fractured porous medium. The mechanical coupling between the two continua is through total stress equilibrium and strain superimposition technique, while the fluid coupling in the two continua is through water exchange term and porosity interaction. The capability of the developed dual porosity poroelastic model is evaluated by comparing the simulated results with that recorded in the laboratory gas injection tests on claystone, in which the main experimental behaviors, i.e., the major gas breakthrough, sample volume dilation, gas induced fracturing are well represented.